High-intensity exercise increases breast milk adiponectin concentrations: a randomised cross-over study - Holmen, Mads; Giskeødegård, Guro F.; Moholdt, Trine (Frontiers in Nutrition, 2023)
Introduction: Adiponectin plays a role in glucose and fat metabolism and is present in human breast milk. It has been postulated that higher breast milk adiponectin concentrations may prevent rapid weight gain in infancy. Prior research indicates that circulating adiponectin increases acutely after endurance exercise, but no prior research has investigated the effect of exercise on breast milk adiponectin concentrations. The purpose of this randomised, cross-over study was to determine the acute effects of endurance exercise on adiponectin concentrations in human breast milk. Methods: Participants who were exclusively breastfeeding a 6-12 week-old term infant (N = 20) completed three conditions in the lab: 1) Moderate-intensity continuous training (MICT), 2) High-intensity interval training (HIIT), and 3) No activity (REST). At each condition, we collected breastmilk at 07:00 hours (before exercise/rest), 11:00 hours (immediately after exercise/rest), 12:00 hours (1 hour after exercise/rest), and 15:00 (4 hours after exercise/rest) and determined adiponectin concentrations using enzyme-linked immunosorbent assay. We compared changes in adiponectin concentrations after MICT and HIIT, adjusted for the morning concentration on each test day, with those after REST, using paired t-tests. Results: Adiponectin concentrations increased 1 hour after HIIT, from 4.6 (± 2.2) μg/L in the 07:00 hours sample to 5.6 (± 2.6) μg/L. This change was 0.9 μg/L (95% confidence interval 0.3 to 1.5) greater than the change between these two timepoints in the REST condition (p = .025). There were no other statistically significant changes in adiponectin concentrations. Conclusion: HIIT may increase adiponectin concentrations in breast milk acutely after exercise. Further studies should determine the impact of exercise-induced elevations in breast milk adiponectin concentrations on growth and metabolism in infancy.